Pengembangan E-Modul Biologi SMA: Kajian Sistematis Literatur - I Made Oka Riawan; Putu Prima Juniartina; Ketut Agustini; I Gde Wawan Sudhata (Universitas Pendidikan Ganesha, 2025)
The advancement of educational technology has driven innovation in the delivery of learning materials, including the development of biology e-modules at the high school level. This systematic literature review (SLR) aims to identify research trends, key topics, keywords, and collaboration patterns related to high school biology e-modules, as well as to map research gaps and future development directions. Articles were selected using the PRISMA method, followed by bibliometric analysis with VOSviewer, which revealed five main clusters: development of instructional materials based on PBL and HOTS, technology integration (AR, VR, Smart Apps, QR Codes), quality validation based on R&D, innovative learning models (PjBL, POGIL), and impact evaluation on student engagement and knowledge retention. The findings indicate that high school biology e-modules are not merely digital materials, but rather a multidisciplinary solution that integrates innovative pedagogy, technology, and contextualized content, including local wisdom such as the Baduy tribe's culture and environmental studies. Collaboration among biologists, educational technologists, and practitioners is essential to address implementation challenges and strengthen education quality. This study recommends the need for continuous development based on longitudinal research and inclusive implementation to ensure long-term impact in supporting education.